Synthesis of cinnamamide derivatives and their α-glucosidase inhibitory activities - Teni Ernawati,; Abdul Mun'im,; Muhamad Hanafi,; Yanuar, Arry (Penerbit Universiti Kebangsaan Malaysia, 2020)
Chemically, methyl trans-cinnamate offers treatment at the three main reactive sites such as substitution at the phenyl ring, addition at the α,β-unsaturation, and substitution at the carboxylic methyl ester functionality. We focus our research to the amide and related derivatives of cinnamates because of their lesser known attributes towards antidiabetic activities. In this research, we modify methyl trans-cinnamate by amidating the carboxylic methyl ester functionality using several amines introduced in functional groups of methyl trans-cinnamate. A series of cinnamamide derivatives was synthesized and evaluated for α-glucosidase inhibitory effects. The structure of synthesized compounds was characterized by IR, melting point, UV, 1H NMR, 13C NMR, and mass spectral analysis. All 13 cinnamamide showed higher α-glucosidase activity than the starting compound. The substitution of cinnamic acid with an amide group altered the α-glucosidase inhibitory activity. Increased bulkiness and the chain length of the amine substituents decreased the inhibitory activity. Propylcinnamamide (3c) showed the most potent inhibitory activity among all the cinnamamide derivatives, all of which act through a competitive inhibitory mechanism. These compounds may be worth exploring further.